The Analysis of Income Gap in Lower Middle-Income Countries - Ardian Dwi Saputro; Siti Aisyah (Universitas Muhammadiyah Yogyakarta, 2023)
Sustainable economic growth is the goal of every country in the world. However, the economic growth that occurs is not in line with the welfare of the population in the lower middle-income countries. The high level of income inequality between the upper and lower classes indicates that there are problems that need to be resolved. This study aims to determine the direction and magnitude of the influence of trade openness, tax revenue, digital economy, corruption perception index, and government spending on the level of income inequality in six countries classified as lower Middle-Income countries in 2017-2021, namely (Bolivia, El Salvador, Honduras, Indonesia, Kyrgyzstan, and Ukraine) using panel data regression. The results with the Fixed Effects approach show that trade openness and the digital economy have a positive effect on the income gap, while government spending has a negative effect on the income gap. Meanwhile, tax expenditures and the corruption perception index have no effect on the income gap. Based on the results of this study, the government in each country should be able to pay attention to the development and support the economic facilities of the people in the lower middle class with various assistances that can directly increase their income.